[tex]\bf ~~~~~~~~~~~~\textit{negative exponents}
\\\\
a^{-n} \implies \cfrac{1}{a^n}
\qquad \qquad
\cfrac{1}{a^n}\implies a^{-n}
\qquad \qquad
a^n\implies \cfrac{1}{a^{-n}}
\\\\
-------------------------------[/tex]
[tex]\bf \left(\cfrac{2}{3}x^{-3}y^4z^2 \right)^3\implies \stackrel{\textit{distributing the exponent}}{\left[\left( \cfrac{2}{3} \right)^3x^{^{-3\cdot 3}}y^{4\cdot 3}z^{2\cdot 3} \right]}\implies \cfrac{2^3}{3^3}x^{-9}y^{12}z^6
\\\\\\
\cfrac{8}{27}\cdot \cfrac{1}{x^9}y^{12}z^6\implies \cfrac{8y^{12}z^6}{27x^9}[/tex]